Differential regulation of excitatory synaptic transmission in the hippocampus and anterior temporal lobe by cyclin dependent kinase 5 (Cdk5) in mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). (14th September 2021) - Banerjee, Jyotirmoy; Srivastava, Arpna; Sharma, Devina; Dey, Soumil; Tripathi, Manjari; Sharma, M.C.; Sarat Chandra, P; Banerjee Dixit, Aparna
Highlights: Cdk5 contributes to excitatory transmission in the patients with MTLE-HS. Cdk5 differentially regulates excitatory transmission in the ATL and Hippocampus. Abstract: Mesial temporal lobe epilepsy with hippocamapal sclerosis (MTLE-HS) is the most common form of drug resistant epilepsy (DRE). MTLE-HS is a distributed network disorder comprising of not only the hippocampus, but other anatomically related extrahippocampal regions. Excitatory synaptic transmission is differentially regulated in the hippocampal and extra-hippocampal regions of patients with MTLE-HS, but its mechanism not understood. Cyclin-dependent kinase 5 (Cdk5) is known to regulate synaptic transmission and plasticity through up-regulation of NMDA receptors by phosphorylating NR2Asubunits. The present study is designed to investigate whether Cdk5 differentially regulates the excitatory synaptic transmission in the hippocampus and anterior temporal lobe (ATL) samples obtained from patients of MTLE-HS. We have measured the Cdk5 kinase activity and the protein levels of Cdk5, p-Cdk5, p35/p25, NR2A, pNR2A in the hippocampal and ATL samples obtained from patients with MTLE-HS. We have also determined the effect of roscovitine, a Cdk5 antagonist, on spontaneous excitatory postsynaptic currents (EPSCs) recorded from the hippocampal and ATL using patch-clamp technique. We observed significant increase in the expression of Cdk5, p-Cdk5, p35/p25, NR2A, pNR2A in the ATL samples as compared to the hippocampal samples. Cdk5 activity was significantly higher in ATL samples as compared to the hippocampal samples. Magnitude of reduction in the frequency of EPSCs by roscovitine in the ATL samples was higher than that in the hippocampal samples. Our studies suggest that Cdk5 differentially regulates excitatory synaptic activity in the hippocampal and ATL region of patients with MTLE-HS.